Collection of All Such Acts of the General Assembly of Virginia, of a Public and Permanent Nature, as are Now in Force, at 187, ch. 103, §§ 8-9 (1803), - (:unkn) unknown (My University, 1792)
Prohibited any "negro or mulatto" from possessing or carrying a gun, powder, shot, club, or other weapon.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES